Peningkatan Kemampuan Menulis Laporan Hasil Observasi dan Keterampilan Berbicara Melalui Model Project Based Learning (PjBL) di Kelas IV MIN 2 AGAM - Rindawati, Aryani; Ratmi Wati, Feli (Journal of Development Education and Learning (JODEL), 2025)
Early-grade literacy encompasses both written and oral communication skills. In MIN 2 Agam, students in grade IV displayed weaknesses in composing observational reports and in oral presentation. This classroom action research aimed to improve students' ability to write observational reports and their speaking skills through Project-Based Learning (PjBL). The study used a two-cycle PTK (Kemmis & McTaggart) with 26 students. Instruments included pre/post-tests for writing and speaking rubrics, motivation questionnaires, observation sheets, and documentation. Writing mastery rose from 30.77% (8/26, mean score 60) pre-intervention to 88.46% (23/26, mean score 85) after Cycle II. Speaking skills (measured by rubric) improved from 34.62% (9/26) to 92.31% (24/26). Motivation for literate activities increased from 35% to 88% in high category. Qualitative data indicated enhanced planning, collaboration, and confidence. PjBL effectively improved both written and oral literacy in grade IV students in the primary school context.